0653 The Relationship Between Sleep And Circadian Rhythm Phenotypes And Dimensions Of Psychotic Experiences - Results From The Oxford Wellbeing Life And Sleep Survey (OWLS). (27th April 2018) - Cosgrave, J; Haines, R; Purple, R J; Porcheret, K; van Heugten-van der Kloet, D; Alexander, I; Juss, A; Johns, L; Goodwin, G; Foster, R; Wulff, K
Abstract: Introduction: Psychotic experiences (PE) are associated with poorer functioning, higher distress, poor sleep, and the onset of serious mental illness. Numerous studies have examined the genetic liability of dimensions in PE - yet relatively little is known about the specificity of environmental and sleep exposures in the prediction of PE dimensions. Using data from the Oxford Wellbeing Life and Sleep (OWLS) survey, the authors examined the severity and specificity of environmental and sleep risks on dimensionally assessed PE. Methods: The OWLS survey included 22 known risk factors for psychosis and 3 sleep related risks (poor sleep quality, insomnia and circadian phase) in a community-based young adult population. Multivariate logistic regression models were fit using these risk factors to predict endorsement of any of six PE dimensions derived from the 16-item Prodromal Questionnaire (PQ-16). Models were built using only 70% of the data, and then fit to the remaining data to assess their generalisability and quality. Results: 1789 (27·2% men; mean age=27·6; SD=10·9) survey responses were analysed. The risk factors predictive of the most PE dimensions were anxiety, social withdrawal during childhood and trauma, followed by cannabis usage and depression. Psychological abuse (during childhood) and poor sleep quality each predicted two dimensions of PE, and the remaining risk factors which reached significance demonstrated specificity to one dimension of PE: age inversely predicted cognitive disorganisation; childhood physical abuse predicted bizarre ideas; childhood bullying and gender predicted persecutory ideation; and circadian phase predicted delusional mood. Conclusion: These results reinforce the notion of a continuum for psychosis, suggesting environmental risk factors for psychotic disorders also increase the risk of different PE dimensions. Furthermore, severity and specificity of risk also varies by PE dimension. Finally, it also highlights the specificity in sleep and circadian exposures in the prediction of different PE dimensions. Support (If Any): The Wellcome Trust.